Analytical Study of Static Observation According to IGS Products - A. Alkanaani, Hayder (International Journal of Engineering and Technology, 2018)
There are many factors affecting the observation accuracy that adopt GNSS technique based on the International GNSS Service (IGS). This can be due to several factors occur in observing process, including satellites and stations clocks, atmospheric parameters, earth crust movement that causes annual changes in the earth's points locations including IGS stations, as well as Earth Polar Motion (EPM). This error ranges from a several centimeters to a few meters. To avoid these errors IGS gave many instructions to increase the observations accuracy in order to reach precise positioning measurements.The objective of this study is to analyze the IGS products and then make a test by observing some points with (Leica Viva GNSS) device and send them to correction by adopt the instructions of this site, which are classified into four broad categories (Broad Cast, Ultra Rapid Predicted and Observed, Rapid, Final). All of these factors are affected by (observing period, Dilution of precision DOP, the timing of data transmission to the relevant site). The accuracy of the observed coordinates are related to these factors. A solution of this problem may be identifying by comparing the OPUS correction with the ideal IGS products to know the difference.Finally, the results of the maximum observing period data (4 hours) and (4 week processing) were compared with the ideal values prepared by the IGS products then specifying the difference value. The results may be adopted as a guide for the surveyor to specify the optimum method of observing.Â Â